Psychological trauma and its impact on a person's life prospects - L. Spytska (Mukachevo State University, 2023)
In psychology, increasingly more attention is being paid to psychological trauma and its impact on people. Psychological trauma poses no less danger to a person and can have a much stronger and more profound impact on their health than a physical illness, and therefore it is necessary to investigate this problem for further effective solution. The purpose of this study was to explore the concept of psychological trauma and its impact on a person's life prospects. The methodology of the study combined theoretical analysis of the literature, the main purpose of which was to define the concept of psychological trauma and its aspects, and empirical research. The empirical stage consisted of a survey and the use of psychodiagnostic techniques. Statistical methods, such as the Mann-Whitney U test and Spearman's correlation coefficient, were used to process the data using the SPSS Statistics software. The findings suggested that people with psychological trauma have a less balanced life perspective, assess the past more negatively, and have higher hopes for the future, which may be a form of compensation for the loss of the past. It was found that the degree of post-traumatic growth depends on the intensity of the trauma. The study substantiated the position that psychotrauma can affect various components of the personality, including motivational, volitional, emotional, and self-esteem. The study confirmed that psychological trauma changes life perspective and can cause disorders in everyday life. It was recommended that for further study of this issue, the subject of research should be narrowed down and psychological approaches to work with survivors of psychological trauma should be developed. The practical significance of this study lies in the development of a comprehensive model of the impact of traumatic events on personality development depending on a range of factors.